Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press - Proscurcin Junior, Pedro (Revista Archai, 2016)
Resenha: Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press